Technology to support integrated Antimicrobial Stewardship Programs: a user centered and stakeholder driven development approach - Nienke Beerlage-de Jong; Lisette Van Gemert-Pijnen; Jobke Wentzel; Ron Hendrix; Liseth Siemons (MDPI AG, 2017)
The rise of antimicrobial resistance (AMR) is a severe global health problem. Tackling this problem requires the prudent prescribing of antimicrobials. This is promoted through Antimicrobial Stewardship Programs (ASPs). In this position paper we describe i) how a socio-technical multidisciplinary approach (based on the CeHRes Roadmap) can be applied in the development and implementation of Antimicrobial Stewardship technologies and ii) how this approach can be of value to support Antimicrobial Stewardship in practice. The CeHRes Roadmap entails five different phases to explore and test how an eHealth technology can be tailored to the target group and successfully implemented in practice: i) contextual inquiry, ii) value specification, iii) design, iv) operationalization, v) evaluation. In this position paper we describe the lessons learned from research and practice to guide future developments of technology based ASP interventions. Since AMR is a huge wicked problem on a global level, it requires innovative methods and models to empower general public and professionals to be proactive rather than reactive in a digitalized world. We highlight how to combat the dangerous rise of antimicrobial resistance in the future.